Before the Barriers Came Up. (Journal of Modern Literature)
In Modernism, Middlebrow, and the Literary Canon: The Modern Library Series, 1917-1955, Lise Jaillant argues that the Modern Library publishing series moved easily and unselfconsciously between the middlebrow and the highbrow in the period before World War II. Only after the war, when cultural anxieties about the dilution of culture began to dominate American intellectual discourse, did this positioning become a contentious issue. Using case studies of Modern Library authors including Sherwood Anderson, William Faulkner, Willa Cather, James Joyce, and H.G. Wells, Jaillant shows that cultural boundaries were much more fluid in the interwar years. Jaillant's study is particularly valuable for its original research in what had seemed an over-studied topic, and for her welcome complication of the commonly oversimplified understanding of the midcentury 'battle of the brows.'